FKBPL and SIRT-1 Are Downregulated by Diabetes in Pregnancy Impacting on Angiogenesis and Endothelial Function - Alqudah, Abdelrahim; Eastwood, Kelly-Ann; Jerotic, Djurdja; Todd, Naomi; Hoch, Denise; McNally, Ross; Obradovic, Danilo; Dugalic, Stefan; Hunter, Alyson J.; Holmes, Valerie A.; McCance, David R.; Young, Ian S.; et al. (Frontiers in Endocrinology, 2021)
Diabetes in pregnancy is associated with preeclampsia, delivery and preterm birth complications. Although the mechanisms leading to these complications are still poorly understood, aberrant angiogenesis and endothelial dysfunction play a key role. FKBPL and SIRT1 are critical regulators of angiogenesis, however, their roles in diabetic pregnancies have not been examined before. Hence, this study aimed to investigate the role of these emerging angiogenesis proteins, FKBPL and SIRT-1, in pre-gestational (type 1 diabetes, T1D) and gestational diabetes (GDM). Placental protein expression of important angiogenesis markers, FKBPL, SIRT-1, PlGF and VEGF-R1, was determined from pregnant women with GDM or T1D, and in the first trimester trophoblast cells exposed to high glucose (30 mM) and varying oxygen concentrations (21%, 6.5%, 2.5% and 1%). Endothelial cell function was assessed in high glucose conditions and FKBPL overexpression. Placental FKBPL protein expression was downregulated in T1D (FKBPL; p<0.05) whereas PlGF/VEGF-R1 were upregulated (p<0.05); correlations adjusted for gestational age were also significant. In the presence of GDM, only SIRT-1 (p<0.001) was significantly downregulated even when adjusted for gestational age (r=-0.92, p=0.001). Both FKBPL and SIRT-1 protein expression was reduced in ACH-3P cells in high glucose conditions and 6.5%/2.5% oxygen concentrations compared to experimental normoxia (21%; p<0.05). FKBPL overexpression in HUVECs reduced tubule formation compared to empty vector control, in high glucose conditions (junctions; p<0.01, branches; p<0.05). In conclusion, FKBPL and/or SIRT-1 downregulation in response to diabetic pregnancies may have a key role in the development of vascular dysfunction and associated complications such as preeclampsia.